2015
DOI: 10.1007/s00432-015-1935-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, exposure and patients’ experiences with the use of erlotinib in non-small cell lung cancer

Abstract: PurposeErlotinib is an orally administered tyrosine kinase inhibitor used for treatment of non-small cell lung cancer. Understanding actual use of medication is essential for optimizing treatment conditions.MethodsIn this multicentre prospective observational study, patients starting erlotinib treatment were followed for 4 months. Adherence was assessed using a medication event monitoring system (MEMS). Area under the curve (AUC) was determined after 1, 2 and 4 months. Before start and at monthly intervals, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 41 publications
3
38
1
Order By: Relevance
“…In studies using MEMS for adherence assessment (Table ), the mean adherence rates ranged between 74 and 100% . Studies assessing the proportion of patients with adherence rates greater than or equal to a threshold of 80% found rates of 75% to 86%.…”
Section: Resultsmentioning
confidence: 99%
“…In studies using MEMS for adherence assessment (Table ), the mean adherence rates ranged between 74 and 100% . Studies assessing the proportion of patients with adherence rates greater than or equal to a threshold of 80% found rates of 75% to 86%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on HCP-related factors influencing non-adherence in patients treated with short-term OACA (e.g. erlotinib, sunitinib) are scarce [10,11].…”
mentioning
confidence: 99%
“…MPR and patient self-rated adherence were significantly correlated (r = 0.68, p < 0.001) in a study of patients with chronic myeloid leukemia (Daouphars et al, 2013). Two separate studies of patients with hematologic malignancies and lung cancer conducted by Timmers et al (2014, 2015) demonstrated a significant association between patient-reported OAM adherence, as captured by MARS, and objective assessments. Walter et al (2013) found, in a study of patients with gastrointestinal malignancies, that patient-reported OAM adherence had a significant positive association with objective pill counts, but not MEMSCap.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies captured patient-reported OAM adherence using the Medication Adherence Rating Scale (MARS) (Timmers et al, 2014, 2015), whereas one employed the Basel Assessment of Adherence Scale (BAAS) (Gebbia et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation